The Impact of Modern Marketing on Quality of Life from the Perspective of Sustainability - Pechočiaková Svitačová, Eva (Studia Ecologiae et Bioethicae, 2026)
Quality of life is linked to consumption, and consumerism is developing in a way that contradicts the paradigm of sustainability. Based on a critical review of literature, the aim of this article is to point out that modern marketing leads to mass consumption and that quality of life is under pressure from consumption, which threatens sustainable development. The article is based on theoretical research, the results of which show that the growth in consumption promoted by contemporary marketing cannot in itself ensure a good quality of life. Moreover, some forms of modern marketing manipulate consumers and restrict their freedom. At the same time, satisfaction of needs is achieved through excessive use of natural resources and at the cost of increasing waste. Given that the purpose of any marketing activity should be people and their quality of life, the article justifies the need for a reform of modern marketing. This would ensure that it focuses primarily on people’s needs and that the relationship between consumption and quality of life is balanced. The humanistic approaches established to marketing should be implemented in marketing practice in the interest of sustainable quality of life.